Directions for a Troubled Discipline – Strategy Research, Teaching and Practice - Jarzabkowski, P; Whittington, R (2008)
This Dialog responds to a growing debate about the relevance of business schools generally and the value of strategy theory and research for strategic management practice. The authors propose that academic theory and management practice can be better connected through management education. The academy researches practice, derives theory, and returns it to practice through the development of teaching materials and the teaching of current and future practitioners. The three articles in this Dialog examine how different approaches to strategy research inform strategy teaching and its application to practice. Joseph Bower explains the rise of business policy and the process research approach that informed that teaching tradition at Harvard Business School. Robert Grant responds by emphasizing the economic theory underpinnings of strategic management research and its impact on teaching. Paula Jarzabkowski and Richard Whittington conclude by proposing a strategy-as-practice perspective and suggesting ways to better incorporate strategy-as-practice research into strategy teaching.